1985
DOI: 10.1016/0009-8981(85)90146-9
|View full text |Cite
|
Sign up to set email alerts
|

Indices for the age of the creatine kinase M-chain in the blood

Abstract: SummaryThe apparent activation energy of the CK reaction as well as the Michaelis-Menten constants and the isoelectric point of CK MM can be used as indices for the mean age of the CK M-chain in the blood in vivo and in vitro. Modifications in the CK M-chain take place in vivo in the blood and in vitro in a serum matrix. Gradual increases in the apparent activation energy are also observed both in vivo and in vitro. It is confirmed that the modification in the CK M-chain causes a rise in the apparent activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Szasz and Gruber [11] have reported marked differences in ap parent Km values between purified and na tive CK MM isoenzyme in human serum. Further, a recent report by Wevers et al [21 ] showed that Km values are influenced by modification of the M chain during the posttranslational aging process.…”
Section: Resultsmentioning
confidence: 99%
“…Szasz and Gruber [11] have reported marked differences in ap parent Km values between purified and na tive CK MM isoenzyme in human serum. Further, a recent report by Wevers et al [21 ] showed that Km values are influenced by modification of the M chain during the posttranslational aging process.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method for the measurement of the catalytic concentration of creatine kinase in serum is based on the principles proposed by Oliver (27) and later modified by Rosalki (28) and by Szasz, Gerhardt 'and co-wprkers in a series of publications (23, 29^· 34). Recommended or Standard methods published by Professional societies in the United Kingdom (35), Federal Republic of Germany (36), the Netherlands (37), France (38), Scandinavia (39,40), and Switzerland (41) are also based on these publications and have also been considered.…”
Section: Principlementioning
confidence: 99%
“…28) estimate the effec ve equilibrium concentrations of Mg-ADP and creatine phosphate to be 1,61 mmol/1 and 25,8 mmol/1, respectively, at the nominal reaction conditions.…”
mentioning
confidence: 99%
“…Because the nucleotide binds to the active site as the magnesium ion complex, magnesium ion concentration is important in establishing the equilibrium concentration ofcomplexed nucleotide. Wevers et al [28] estimated that the effective equilibrium concentrations of Mg-ADP and creatine phosphate were 1. '61 mmol/1 and 25"8 mmol/1, respectively, at the nominal reaction conditions.…”
Section: Buffer Typementioning
confidence: 99%